Development of a mathematical model for predicting postoperative pain among patients with limb injuries - Georgiyants, Marine; Khvysyuk, Oleksandr; Boguslavskaуa Natalіya; Vysotska, Olena; Pecherska, Anna (Eastern-European Journal of Enterprise Technologies, 2017)
A mathematical model is devised to predict the probability of development of postoperative pain among patients of young age, operated on in a planned manner for the limb injuries. As the model predictors we selected: the level of pain before operation, determined by the visual analog scale, result of evaluation of cognitive abilities by the Montreal scale and level of the mean blood pressure. The application of the developed model makes it possible to improve quality of providing the patients with anesthesiological assistance. The results obtained might be used in the development of information decision support system for a physician-anaesthesiologist for the objectification and automation of the process for determining the probability of development of postoperative pain syndrome. The introduction of such a system into clinical practice will make it possible to reduce the load on the medical staff and decrease the amount of anaesthetising preparations for patients, whose value of the level of pain before operation, determined by the visual analog scale after the operation, does not exceed 3 points, as well as to conduct more adequate analgesia among patients with a higher value of this indicator.